If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1y = 65 Solving 2x + -1y = 65 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 2x + -1y + y = 65 + y Combine like terms: -1y + y = 0 2x + 0 = 65 + y 2x = 65 + y Divide each side by '2'. x = 32.5 + 0.5y Simplifying x = 32.5 + 0.5y
| 7x-3=3x+10 | | 25x+10y-10=0 | | 2.25+0.014x=2.5+(175-x)*0.014 | | R(x)=-2.5x^2+500x | | 25x+10y=0 | | 14.5=12y | | 18=-6y+3(y-3) | | (x+y)dy+(x-y)dx=0 | | 100x^2-1000=0 | | 2.25+0.14x=2.5+(175-x)*0.014 | | 2.25+0.014x=1.5+(175-x)*0.014 | | 2.25+0.14x=1.5+(175-x)*0.014 | | -8.8=12y | | 3x-15=9x+9 | | (8-v)(2v-3)=0 | | 7m-20=36 | | 1/3-6x=12 | | 72=3w+12 | | 5m+3=48 | | 2y-4=-10 | | 4x+5yi=-12+15i | | -4x+6=-6x+11 | | 3=3(y-8)-6y | | 3(4x+5yi)=-36+45i | | 4v+4v=v | | 9.36m-2.021=8.89k | | 4y-8x+12= | | -7(8-5s)=-20 | | -5x-3=-9x-3-2x | | -14y+8y=-12 | | x+3x+33x=150 | | 511=3+2(x-5) |